World Who is Who and Does What in Environment and Conservation - Earthscan; Polunin Nicholas (1997)
A valuable guide for policy makers, lobbyists, researchers and students wishing to stay current on the vast array of organizations and individuals involved in the global environmental movement. Introduction, Dedication in Memoriam, Biographies, Appendix I by Country, Appendix II by Specialty, Appendix III abbreviations and Acronyms and Contractions and Some Explanations.